PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN GRIYA ARDHYA GARINI MADIUN - Wagiyem, Wagiyem; Triyanto, Triyanto; Adelina, Nina; Kusmiati, Dewi (Riset Manajemen dan Akuntansi, 2023)
Many corporate institutions or housing providers use the concept of the marketing mix as a strategy to attract potential customers to improve consumer purchasing decisions, especially housing. This study aims to determine the effect of marketing mix product, price, location and promotion on purchasing decisions of Griya Ardhya Garini Madiun Housing. This research is a descriptive research with a quantitative approach. The population of all consumers of Griya Ardhya Garini Madiun housing as many as 313 people was taken by Simple Random Sampling using slovin obtained a sample of 76 people. The research instrument was a questionnaire with a Likert scale. The data analysis technique used multiple linear regression analysis. The results showed that the product marketing mix, price, location and promotion had a significant effect on purchasing decisions. Price marketing mix has the most dominant influence on housing purchase decisions. Based on the analysis of the coefficient of determination result obtained that the adjusted r square value of 0,634 means that variations in housing purchasing decisions can be influenced by the product marketing mix, price, location and promotion variables of 63,4%.